Effective and sensitive determination of eleven disinfection byproducts in drinking water by DLLME and GC-MS - On, Jiwon; Pyo, Heesoo; Myung, Seung-Woon (ELSEVIER, 2018)
The aim of this study was to optimize the dispersive liquid-liquid microextraction (DLLME) parameters for simultaneous analysis through DLLME-gas chromatography-mass spectrometry (GC-MS) of six iodo-trihalomethanes, four haloacetonitriles, and one halonitromethane, which are residual disinfection products found in drinking water. Eleven disinfection by-product (DBPs) remaining in aqueous samples were extracted and concentrated using a simple, rapid, and environmentally friendly DLLME method, and then analyzed simultaneously by GC-MS. The optimized DLLME parameters were a sample volume of 5 mL, 100 mu L of dichloromethane as the extraction solvent, 1 mL of methanol as the dispersion solvent, an extraction time of 60 s, and 1.5 g of sodium chloride for the salting out effect. The enrichment factor values obtained using the established DLLME-GC-MS method were 19.8-141.5, and the limit of detection and limit of quantification were 0.22-1.19 mu g/L and 0.75-3.98 mu g/L, respectively. The calibration curves had correlation coefficients (r(2)) of 0.9958-0.9992 in the concentration range of 0.5-40 mu g/L, and they exhibited good linearity in quantitative analysis. This new method could be useful for analyzing eleven DBPs that remain in drinking water. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: LIQUID-LIQUID MICROEXTRACTION; IODINATED TRIHALOMETHANES; PHASE MICROEXTRACTION; IODO-TRIHALOMETHANES; CELL CYTOTOXICITY; HALOACETIC ACIDS; N-NITROSAMINES; IMPACT; CHLORINATION; HALOACETONITRILES